Impact of a Mindfulness-Based Intervention on Basic Psychological Need Satisfaction and Internalized Symptoms in Elementary School Students With Severe Learning Disabilities: Results From a Randomized Cluster Trial - Malboeuf-Hurtubise, Catherine; Taylor, Geneviève; Mageau, Geneviève A. (Frontiers in Psychology, 2019)
Background: Mindfulness is hypothesized to lead to more realistic appraisals of the three basic psychological needs, which leads people to benefit from high levels of need satisfaction or helps them make the appropriate changes to improve need satisfaction. Mindfulness-based interventions (MBIs) have shown promise to foster greater basic psychological need satisfaction in students with learning disabilities (LDs). Objective: The goal of the present study was to evaluate the impact of a MBI on the satisfaction of the basic psychological needs and on internalized symptoms in students with severe LDs. A randomized cluster trial was implemented to compare the progression of need satisfaction, anxiety and depression symptoms in participants pre-to-post intervention and at follow-up. Method: Elementary school students with severe LDs (N = 23) in two special education classrooms took part in this study and were randomly attributed to either an experimental or an active control group. Results: Looking at within-subject differences on participants’ scores of autonomy, competence and relatedness across time, we found a significant main effect for the competence need (Wilks Lambda = .66, F (2, 42) = 5.10, p= .02, partial η2=.34). Post-hoc analyses showed that for both groups, scores were significantly higher at post-intervention (p = .03) and at follow-up (p = .04), when compared to pre-intervention scores. A significant main effect was also found for anxiety levels over time (Wilks Lambda = .61, F (2, 42) = 6.19, p= .008, partial η2=.38). Post-hoc analyses showed that for both groups, scores were significantly lower at post-intervention (p = .01) and at follow-up (p = .006), when compared to pre-intervention scores. Conclusion: Although the MBI was useful in increasing the basic psychological need of competence and decreasing anxiety symptoms in students with severe LDs, it was not more useful than the active control intervention that was used in this project. Future studies should verify that MBIs have an added value compared to other types of interventions that can be more easily implemented in school-based settings.